Pengaruh Modernisasi Penjualan Kopi Jago Melalui Gerobak Keliling Terhadap Kepuasan Pelanggan - Nur Kholifatun Nisa; Riza Fahlapi; Cahaya Tamara; Azzahra Putri Zudanti; Sabitah Munifah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of sales modernization applied by Kopi Jago through its mobile coffee carts on customer satisfaction. A quantitative approach was used by distributing questionnaires to 110 respondents who had purchased Kopi Jago products. The collected data were processed using validity and reliability tests, classical assumption testing, multiple linear regression analysis, as well as t-tests and F-tests. The results indicate that price, product quality, service, and brand image each have a positive and significant effect on customer satisfaction. Simultaneously, these four variables contribute substantially, with a determination value of 88.4%. These findings demonstrate that Kopi Jago’s modern sales concept effectively enhances customer experience and strengthens the brand’s position in the coffee market